PRELIMINARY STUDY: CHEMISTRY LABORATORY VIRTUAL INNOVATION AS AN OPTIMIZATION OF SCIENCE LEARNING DURING THE COVID-19 PANDEMIC - Bayu Antrakusuma; Nurma Yunita Indriyanti; Meida Wulan Sari (JURNAL PENA SAINS, 2021)
The purpose of this research is to conduct a preliminary study to create a virtual chemistry laboratory innovation to optimize learning during the Covid-19 pandemic in the Natural Science Education Study Program of the Teacher Training and Education Faculty Universitas Sebelas Maret (FKIP UNS). The Natural Science Education Study Program of FKIP UNS itself teaches chemical concepts that require laboratory activity. This study used the descriptive qualitative method. Data was collected using observation, interviews, and analysis of related documents and equipped with a Focus Group Discussion (FGD) with students and lecturers (Science Education and Chemistry Education FKIP UNS). The results showed that 11 chemistry practicums required virtual laboratory innovation in the Natural Science Education Study Program of FKIP UNS due to restrictions on the use of laboratories by the campus. It was concluded that a virtual chemistry laboratory was needed as an alternative to student practicum activities to maintain and optimize laboratory skills in online learning. In addition, the developed virtual laboratory needs to be embedded online and can be accessed through various gadgets so that it can be used anytime and anywhere.